Bermain dan kompetensi sosial anak: Studi meta-analisis - Iswinarti Iswinarti (Universitas Muhammadiyah Malang, 2014)
The purpose of this study was to examine the relation between play and social competence in childrenusing meta-analytic of 20 study from 17 articles. The articles consisted of 10 experimental and 7 survey literature. Summary analysis did not support the hypothesis that play has a positive correlation on social competence in children. The result showed that the relation between play and social competencenot always positive. Explaining about what kinds of play influencing social competence was used to discuss why the hypothesis did not accepted.